Intrinsic religiosity protects believers from the existential fear of a human Jesus. Issue 5 (28th May 2018) - Arrowood, Robert Britton; Cox, Cathy R.; Weinstock, Maddie; Hoffman, Jill
ABSTRACT: The present study examined the role of internalised religious beliefs in defending against existential concerns aroused from a creaturely Jesus. Prior work has found that biologically human traits (e.g., vomiting, sweating, etc.) can increase death concerns when applied to both humans and a god. Intrinsic beliefs, however, have been shown to reduce mortality awareness. In the current study, religious participants were primed with thoughts of either a human or neutral Jesus followed by a single item measure about fear of death. A moderated regression analysis found that whereas high intrinsic individuals were buffered from existential concerns, low intrinsic individuals experienced a greater fear of death when primed with a human Jesus. These results replicate prior work within terror management theory and the psychology of religion suggesting that internalised beliefs serve a protective function against existential anxieties.